Assess the Knowledge, Practice and Attitude Regarding Nosocomial Infections and their Preventive among Health Care Staf (Medico Legal Update, 2021)
Nosocomial infections are diseases acquired within 48 hours or more of hospital admission or within 30days of discharge. The objectives of the study were to assess the knowledge, attitude and practice regardingnosocomial infection and their prevention among health care workers. To determine the relationshipbetween knowledge, attitude and practice regarding nosocomial infection and their prevention among healthcare workers. To find out association between the knowledge, attitude and practice regarding nosocomialinfection and their prevention among health care workers. The research design selected for the study wasdescriptive research design and a total 100 health care staff were selected as study sample tool was usedfor data collection. Self-introduction was given and purpose of gathering the information and nature ofstudy was explained before taking information through non probability convenient sampling technique. Aself- structured questionnaire, consent was signed by participants. The result revealed that the most of thehealth care staff 76(76%) had excellent knowledge regarding nosocomial infection and their preventionless than half, 43(43%) had positive attitude regarding nosocomial infection and their prevention. On thecontrary, 74(74%) had excellent practice regarding nosocomial infection and their prevention. On applyingthe spearman correlation test, relationship between knowledge and attitude was found to be significantat p